Safety of exercise therapy after acute pulmonary embolism. (December 2020) - Cires-Drouet, Rafael S.; Mayorga-Carlin, Minerva; Toursavadkohi, Shahab; White, Rachel; Redding, Emily; Durham, Frederick; Dondero, Kathleen; Prior, Steven J.; Sorkin, John D.; Lal, Brajesh K
Objective: The role of exercise therapy after acute pulmonary embolism (PE) is unknown. Exercise therapy is safely used after myocardial infarction and chronic obstructive pulmonary disease. The aim of this study was to investigate the safety of exercise therapy after acute PE. Methods: We implemented a 3-month exercise program after acute PE. Outcomes were death, bleeding, readmissions, recurrent events, changes in peak VO2 and quality of life (QoL). Results: A total of 23 patients were enrolled and received anticoagulation; no adverse events were reported during the exercise period. One death, 1 DVT and 5 readmissions were reported due to non-exercise related reasons. Functional capacity improved as evidenced by an increased peak VO2 at 3 months (+3.9 ± 5.6 mL/kg/min; p = 0.05). Improvement in QoL was observed at 6-months on the functional (+17.0 ± 22.6, p = 0.03) and physical health factor scales (+0.9 ± 4.6, p = 0.03). Conclusion: Exercise therapy is feasible and safe in appropriately anticoagulated patients after PE.